Absolute Nothingness - The Kyoto School and Sound Art Practice - Roddy, Stephen (My University, 2017)
This paper explores how the concept of Absolute Nothingness as developed in the thought of three key Kyoto School thinkers Nishida Kitarō, Tanabe Hajime and Nishitani Keiji has influenced the practice of sound art. The paper examines the influence of these three philosophers on D.T. Suzuki and John Cage, the Mono-ha movement, and the Fluxus movement before examining how these influences have shaped sound art practice.
The Proceedings of Invisible Places 2017
Invisible Places
Keywords: Kyoto; School; Absolute; Nothingness; Sound; Art; Nishida; Tanabe; Nishitani; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Installation & sound art; Kyoto School; Sound Art; Community; Culture; History